IMPLEMENTASI KURIKULUM 2013 DALAM PROSES PEMBELAJARAN MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI 1 BANTUL - Ermawati Ermawati (Universitas Sarjanawiyata Tamansiswa, 2016)
This study aimed to describe: 1) the implementation of the curriculum in 2013 in the learning process; 2) the constraints experienced by the teachers during the learning process Indonesian subjects in SMP Negeri 1 Bantul. This study used a qualitative descriptive approach in the form of case studies with research taking place in SMP Negeri 1 Bantul, Bantul, Yogyakarta Province. Sources of data in this research are the process of teaching belajajar, informants, and documents. Data collected by observation, interviews and document analysis. Test the validity of the data is done by triangulation method, triangulation of sources and informants review. Data analysis techniques with interactive analysis include data reduction, data presentation, and drawing conclusions or verification. Based on the findings in the field can be concluded that: 1) Preparatory activities, new learning objectives contains elements of Behavior (B) and Condition (C); Core activities, teachers have been working to create learning (student center) in terms of materials, approaches, methods, and media; closing activity, students rarely provided feedback; 2) activity of students in participating in learning activities has not been optimal; There are teachers who lack optimize, facilities and infrastructure in learning activities; reference is still limited (the learning material focuses on textbooks revised edition 2016).